Synthesis and Application to Polyester and Nylon 6 Fabrics of Hetaryl Bis-Azo Disperse Dyes Based on 6-Amino-2,4-Dihydroxypyrimidine and 4-Methoxy-2-Nitroaniline Moieties - Otutu, O. J.; Asiagwu, A. K. (Journal of Scientific Research, 2019)
Six new bis-azo disperse dyes were synthesized by linking various aryl amino and hydroxyl derivatives to 4-methoxy-2-nitroaniline and 6-amino-2,4-dihydroxypyrimidine moieties through diazo coupling reactions. The structures of the bis-azo dyes were identified by Fourier transform infrared, proton and carbon 13 nuclear magnetic resonance data. The prepared dyestuffs were applied onto polyester and nylon 6 fabrics and subsequently their fastness properties in terms of light, washing, sublimation and rubbing were determined. Compared with the light fastness of polyester fabrics, the light fastness of the dyed nylon 6 fabrics were slightly lower. The technical performance of the dyes on the two textile substrates used for the study, demonstrated their useful applications in the dyeing of synthetic fibres.